Policy Implementation Analysis of Antenatal Care Services at Puskesmas Negara Ratu and Puskesmas Cempaka Kabupaten Lampung Utara - Syafriyanti, Willyana; Achadi, Anhari (UI Scholars Hub, 2024)
The Ministry of Health has issued Minister of Health Regulation Number 21 of 2021 to strengthen maternal health services, which regulates health services during pregnancy (antenatal). The Minister of Health's regulation states that antenatal care is carried out at least six times, 2 (two) of which are examinations with a doctor using an Ultra Sonography (USG) device. Community health centers as primary services are expected to be able to provide antenatal services according to standards. The North Lampung Health Service has distributed ultrasound equipment to community health centers in the North Lampung Regency to support the implementation of antenatal services. The research aims to determine the implementation of antenatal care policies at the Negara Ratu Health Center and Cempaka Health Center. This research is qualitative with a case study design; data was collected through in-depth interviews, observation, and document review. The research results show that implementing the antenatal care policy at the Community Health Center has been running according to the 10 T standard, including antenatal care with doctors using ultrasound equipment. However, integrated antenatal care with mental health programs, recording in the mother's KIA book, and reporting K6 coverage by the Community Health Center have not been implemented optimally. Human resources and facilities still need to be improved. Even though most pregnant women support and participate in antenatal care, obstacles, and challenges are still found in encouraging the participation of pregnant women. Efforts are needed to optimize the implementation of antenatal care policies and increase resources and community support to support the implementation of antenatal care policies at Community Health Centers.